Qira’at Al-Qur’an: Genealogi Kemunculan dan Perbedaan Bacaan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
The study of Qira'at (Quranic recitations) holds a crucial position in the scholarly discourse on the Quran, focusing on the theoretical aspects of accurately reciting its verses. The Quran is characterized by its extensive variety of recitations, historically rooted in the teachings of Prophet Muhammad. This diversity often leads to confusion and skepticism among the public regarding the authenticity of the Quranic readings. This article aims to explore the genealogy of the variations in Qira'at, including their origins, contributing factors, and the wisdom behind these variations. Our research indicates that the emergence of different Qira'ats is attributed to both internal and external factors: internally, the Prophet's request to Allah for additional variations in recitation, as evidenced by numerous narratives on the revelation of the seven Ahruf (modes of recitation), and externally, the perspectives of orientalists such as Arthur Jeffery, Theodore Noldeke, and Ignaz Goldziher, who argue that these variations arose due to the absence of vowel and consonant markings in the original text. The benefits of Qira'at diversity include reinforcing Islamic unity, facilitating easier and more accessible recitation across various dialects, and highlighting the miraculous nature of the Quran and Allah’s favor towards the followers of Prophet Muhammad SAW.Abstrak: Ilmu Qira'at adalah bidang studi penting dalam disiplin ilmiah Al-Quran, fokusnya adalah pada teori dan praktik membaca ayat-ayat Al-Quran secara akurat. Al-Quran dikenal memiliki beragam variasi bacaan, yang berakar dari pengajaran Nabi Muhammad SAW. Variasi ini sering kali menimbulkan kebingungan dan skeptisisme terhadap autentisitas bacaan Al-Quran di kalangan masyarakat. Artikel ini bertujuan untuk membahas genealogi perbedaan qira'at, mencakup asal-usul, faktor penyebab, dan manfaat dari variasi qira'at tersebut. Penelitian menunjukkan bahwa perbedaan qira'at muncul dari dua faktor utama: faktor internal, seperti permintaan Nabi kepada Allah untuk menambah variasi dalam cara bacaan yang dibuktikan dengan banyaknya riwayat tentang sab’ah al-qira’at, dan faktor eksternal, termasuk pandangan orientalis seperti Arthur Jeffery, Theodore Noldeke, dan Ignaz Goldziher yang berargumen bahwa perbedaan tersebut timbul karena ketiadaan tanda vokal dan konsonan pada teks asli. Manfaat dari variasi qira'at ini termasuk memperkuat kesatuan umat Islam, memudahkan pembacaan dengan berbagai dialek, serta menegaskan keajaiban Al-Quran dan keistimewaan umat Nabi Muhammad SAW.
Keywords: Qira’at; Faktor; Perbedaan; Hikmah